Parasitic nematode secreted phospholipase A2 suppresses cellular and humoral immunity by targeting hemocytes in Drosophila melanogaster - Parks, Sophia C.; Okakpu, Ogadinma K.; Azizpor, Pakeeza; Nguyen, Susan; Martinez-Beltran, Stephanie; Claudio, Isaiah; Anesko, Kyle; Bhatia, Anil; Dhillon, Harpal S.; Dillman, Adler R. (Frontiers in Immunology, 2023)
A key aspect of parasitic nematode infection is the nematodes’ ability to evade and/or suppress host immunity. This immunomodulatory ability is likely driven by the release of hundreds of excretory/secretory proteins (ESPs) during infection. While ESPs have been shown to display immunosuppressive effects on various hosts, our understanding of the molecular interactions between individual proteins released and host immunity requires further study. We have recently identified a secreted phospholipase A2 (sPLA2) released from the entomopathogenic nematode (EPN) Steinernema carpocapsae we have named Sc-sPLA2. We report that Sc-sPLA2 increased mortality of Drosophila melanogaster infected with Streptococcus pneumoniae and promoted increased bacterial growth. Furthermore, our data showed that Sc-sPLA2 was able to downregulate both Toll and Imd pathway-associated antimicrobial peptides (AMPs) including drosomycin and defensin, in addition to suppressing phagocytosis in the hemolymph. Sc-sPLA2 was also found to be toxic to D. melanogaster with the severity being both dose- and time-dependent. Collectively, our data highlighted that Sc-sPLA2 possessed both toxic and immunosuppressive capabilities.